Considering the Other Half of the Gut Microbiome: Bacteriophages - Corinne F. Maurice (American Society for Microbiology, 2019)
ABSTRACT Bacteriophages, viruses specific to bacteria, regulate bacterial communities in all known microbial systems. My research aims to determine how they interact with the trillions of bacteria found in the human gut. To do this, I apply a whole-systems perspective on both communities, considering bacteriophage replication cycles, bacterial and bacteriophage diversity, temporal dynamics, interactions, and responses to perturbations. Building upon ecological concepts and an array of independent and complementary techniques, I study the human gut from a microbial perspective. In contrast with bacteria, working with bacteriophage communities comes with many significant challenges, starting with the limited experimental toolkit and curated databases. Yet an increasing number of studies are pushing these scientific boundaries every day. In the human gut, future research that includes bacteriophages will lead to many exciting and warranted research avenues. From phage therapy and immunization to targeted drug delivery, the sky is the limit in my opinion.